2021
DOI: 10.1111/phpp.12718
|View full text |Cite
|
Sign up to set email alerts
|

Blue light induces DNA damage in normal human skin keratinocytes

Abstract: Blue light (400-500 nm) takes part of the visible electromagnetic spectrum. Natural sunlight blue wavelengths, which are always mixed with green, yellow, and red wavelengths, have been shown to play an important role in the regulation of sleeping patterns and circadian rhythms. 1 However, since the 1980s the development of lightemitting diodes (LED) without red and near-infrared wavelengths and the concomitant exponential use of digital technologies, such as flat-screen TVs, computers, tablets, and smartphones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Therefore, it could be of interest in the future to perform modified alkaline COMET assays, using formamidopyrimidine‐DNA glycosylase and T4 endonuclease V, 7,65 to gain more insight into the generation of DNA damage by HEV/blue light. This approach was recently used in conjunction with micronucleus assays in the study by Chamayou‐Robert et al 66 . to show that exposure to a single dose of blue light at 415 nm generates both oxidized DNA bases and CPDs, which may result in chromosome aberrations in human keratinocyte cultures.…”
Section: An Innovative Spf50+ Sunscreen Containing Triasorbmentioning
confidence: 99%
“…Therefore, it could be of interest in the future to perform modified alkaline COMET assays, using formamidopyrimidine‐DNA glycosylase and T4 endonuclease V, 7,65 to gain more insight into the generation of DNA damage by HEV/blue light. This approach was recently used in conjunction with micronucleus assays in the study by Chamayou‐Robert et al 66 . to show that exposure to a single dose of blue light at 415 nm generates both oxidized DNA bases and CPDs, which may result in chromosome aberrations in human keratinocyte cultures.…”
Section: An Innovative Spf50+ Sunscreen Containing Triasorbmentioning
confidence: 99%
“…It was suggested that violet-blue light, also known as high-energy visible light, causes ROS formation in the skin, which induces a decrease of the carotenoid concentration in the SC. Subsequently, the ROS formation in the skin that is caused by exposure to visible light was confirmed in an in vivo study of human skin using EPR spectroscopy [ 158 ] and in numerous studies evaluating oxidative stress-induced changes in the skin subsequent to irradiation with visible light [ 159 , 160 , 161 ].…”
Section: Factors Resulting In the Reduction Of Carotenoids In The Scmentioning
confidence: 99%
“…Sunscreens are the other pillar of prevention: their use is recommended by all guidelines [9,[51][52][53] as RCTs have demonstrated that sunscreen use reduces the occurrence of both AKs and SCCs [54][55][56]. The preventative action of sunscreens will likely be further increased by new filters with better photo-stability and water resistance [57] and will be able to shield not only UVB but also UVA and blue light, which have demonstrated mutagenic activity on keratinocytes [57,58]. Oral photoprotection and chemoprevention treatments are also attracting increasing attention: oral nicotinamide (or niacinamide) is a low-cost compound that has demonstrated to both prevent and reduce the number of AKs in high-risk patients, i.e., patients who had at least two non melanoma skin cancers (NMSCs) in the previous 5 years [59].…”
Section: Oral and Topical Photoprotection And Chemoprevention Of Aksmentioning
confidence: 99%
“…Sunscreens are the other pillar of prevention: their use is recommended by all guidelines [ 9 , 51 53 ] as RCTs have demonstrated that sunscreen use reduces the occurrence of both AKs and SCCs [ 54 56 ]. The preventative action of sunscreens will likely be further increased by new filters with better photo-stability and water resistance [ 57 ] and will be able to shield not only UVB but also UVA and blue light, which have demonstrated mutagenic activity on keratinocytes [ 57 , 58 ].…”
Section: Oral and Topical Photoprotection And Chemoprevention Of Aksmentioning
confidence: 99%